2013
DOI: 10.1155/2013/293643
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Structure of Purkinje Fibers in the Heart of Ostrich (Struthio camelus) with the Special References on the Ultrastructure

Abstract: Purkinje fibers or Purkinje cardiomyocytes are part of the whole complex of the cardiac conduction system, which is today classified as specific heart muscle tissue responsible for the generation of the heart impulses. From the point of view of their distribution, structure and ultrastructural composition of the cardiac conduction system in the ostrich heart were studied by light and electron microscopy. These cells were distributed in cardiac conducting system including SA node, AV node, His bundle and branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Though past research has suggested the possibility of more active conduction in the left ventricle, our research seemed to indicate no significant difference between the two regions [[12], [13], [14],31]. This is in keeping with the other results of this study, given that Purkinje fibers are present in both ventricles [15,32].…”
Section: Discussionsupporting
confidence: 85%
“…Though past research has suggested the possibility of more active conduction in the left ventricle, our research seemed to indicate no significant difference between the two regions [[12], [13], [14],31]. This is in keeping with the other results of this study, given that Purkinje fibers are present in both ventricles [15,32].…”
Section: Discussionsupporting
confidence: 85%
“…Indirectly, the argument in favor of this opinion is the fact that thickening of the MV occurs when RV hypertrophy is developed in birds (Pees et al, 2001;Stedman and Brown, 2002;Pees et al, 2006). One more reason for this opinion is the presence of conducting myocytes in the MV (Davies, 1930;Prosheva, 1986;Lu et al, 1993;Parto et al, 2013). As it is known, mainly the conduction system is responsible for the excitation pattern in the heart of endothermic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the presence of conducting myocytes in the avian MV was proved by electrophysiology and electron microscopy (Prosheva, 1986;Lu et al, 1993;Parto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…; Parto et al. ; Prosheva & Kaseva, ). As known, conducting myocytes are mainly responsible for the excitation pattern in the heart ventricles of endothermic animals.…”
Section: Discussionmentioning
confidence: 97%